2012
DOI: 10.1242/jcs.088302
|View full text |Cite
|
Sign up to set email alerts
|

Force transduction and strain dynamics in actin stress fibres in response to nanonewton forces

Abstract: SummaryIt is becoming clear that mechanical stimuli are crucial factors in regulating the biology of the cell, but the short-term structural response of a cell to mechanical forces remains relatively poorly understood. We mechanically stimulated cells transiently expressing actin-EGFP with controlled forces (0-20 nN) in order to investigate the structural response of the cell. Two clear force-dependent responses were observed: a short-term (seconds) local deformation of actin stress fibres and a long-term (min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
92
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 57 publications
(104 citation statements)
references
References 68 publications
10
92
2
Order By: Relevance
“…By altering tip geometry or chemistry, a multitude of both local and whole-cell studies can be performed on living cells in their native environments (figure 3). Studies of this nature have been shown to induce a rapid response of cells through shape change, remodelling of the cytoskeleton and calcium signalling, which all depend on frequency, duration, magnitude and location of applied force [9,29,37,102]. In the following sections, we discuss the role of AFM in measuring the mechanical properties of cells, particularly cell stiffness and viscous properties.…”
Section: Nanomechanics Using Atomic Force Microscopymentioning
confidence: 99%
See 1 more Smart Citation
“…By altering tip geometry or chemistry, a multitude of both local and whole-cell studies can be performed on living cells in their native environments (figure 3). Studies of this nature have been shown to induce a rapid response of cells through shape change, remodelling of the cytoskeleton and calcium signalling, which all depend on frequency, duration, magnitude and location of applied force [9,29,37,102]. In the following sections, we discuss the role of AFM in measuring the mechanical properties of cells, particularly cell stiffness and viscous properties.…”
Section: Nanomechanics Using Atomic Force Microscopymentioning
confidence: 99%
“…Details on these methods [106] as well as Young's moduli of a variety of cell types are listed in [35]. Apparent stiffness of mammalian cells, as measured with AFM, typically ranges between 1 and 100's of kPa [9,107,108]. Apparent cell stiffness is highly correlated with the stiffness of the actin cytoskeleton, the structure and mechanics of which are directly influenced by mechanical forces including tension/compression [109,110], hydrostatic and osmotic forces [31,99].…”
Section: Apparent Cell Stiffnessmentioning
confidence: 99%
“…Guolla et al also have reported the strain dynamics in actin stress fibers in response to applied external force [10]. They conducted simultaneous observation of atomic force microscopy (AFM) and fluorescent microscopy, and evaluated the precise strain dynamics in actin stress fibers.…”
Section: Comparison Between Measured Stress Fiber Deformation and Estmentioning
confidence: 99%
“…D1306). A full protocol has been published previously [27]. Samples were then mounted using Vectashield (Vector Labs) and a no.…”
Section: Immunofluorescence Staining Quantification Time-lapse Imagmentioning
confidence: 99%